Implicit Detection Observation in Different Features, Exposure Duration, and Delay During Change Blindness - Xiang, Wang (Frontiers in Psychology, 2021)
To investigate whether implicit detection occurs uniformly during change blindness with single or combination feature stimuli, and whether implicit detection is affected by exposure duration and delay, two one-shot change detection experiments are designed. The implicit detection effect is measured by comparing the reaction times (RTs) of baseline trials and change blindness trials. If the RTs of blindness trials are longer than that of baseline trials, implicit detection has occurred. The strength of the implicit detection effect was measured by the difference in RTs between the baseline and change blindness trials, where the larger the difference, the stronger the implicit detection effect. Both in Experiments 1 and 2, the results showed that the RTs of change blindness trials were significantly longer than that of baseline trials. Whether under set sizes 4, 6, or 8, the RTs of the change blindness trials were significantly longer than in the baseline trials. In Experiment 1a, when the exposure duration was shorter, the difference between the baseline and change blindness trials’ RTs was smaller. In Experiment 2, when the delay was longer, the difference between the two trials’ RTs was larger. These results suggest that regardless of whether the change occurs in a single or a combination of features and whether there is a long exposure duration or delay, implicit detection occurs uniformly during the change blindness period. Moreover, longer exposure times and delays strengthens the implicit detection effect. Set sizes had no significant impact on implicit detection.